Supported iridium-containing catalyst as well as preparation method and application thereof
By using yttrium-doped titanium oxide-containing catalysts to support iridium-containing catalysts, the problem of high cost of anode catalysts in proton exchange membrane electrolysis hydrogen production technology is solved, and the catalytic effect is achieved with high activity, low overpotential and stability is achieved, reducing the Precious metal usage.
Patent Information
- Application Number
- CN202310865317.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-14
AI Technical Summary
The existing proton exchange membrane electrolytic hydrogen production technology is costly, which restricts its large-scale development, especially the lack of effective support materials in anode catalysts, which affects the utilization rate and catalytic activity of precious metals.
A yttrium-doped titanium oxide compound is used as a support and an iridium-containing substance is supported as an active component. A support-type iridium-containing catalyst is prepared by contact reaction method to improve the oxidation resistance and acid resistance of the catalyst, and reduce the amount of precious metals.
The proton exchange membrane electrolytic hydrogen production anode catalyst has low overpotential, high activity and good cycle stability, which reduces costs and improves the precious metal utilization and catalytic activity of the catalyst.
Smart Images

Figure CN119307960A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of hydrogen energy and electrocatalysis technology, and in particular, to a supported iridium-containing catalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen is a clean and flexible energy carrier. It can be produced from traditional fossil fuels such as coal, oil, and natural gas, as well as clean energy such as wind and solar energy. Renewable energy electrolysis hydrogen production is considered the cleanest method for producing hydrogen. The produced hydrogen meets the concept of "green hydrogen". Countries around the world are also actively promoting the research and application of technologies related to renewable energy hydrogen production. As the basis for renewable energy hydrogen production, water electrolysis hydrogen production technology has received increasing attention.
[0003] Among them, proton exchange membrane (PEM) water electrolysis technology has been gradually promoted at home and abroad due to its advantages of high efficiency, fast start and stop, small size, and high purity of hydrogen production. However, the cost of PEM water electrolysis hydrogen production is currently high, which restricts its large-scale development. By loading precious metal catalysts on carriers, the amount of precious metals can be greatly reduced, and the cost can be reduced without affecting the active precursors.
[0004] Introducing appropriate carriers to prepare supported catalysts is an effective method to improve the utilization rate of precious metals and the activity of catalysts. The introduction of carriers improves the dispersion effect of precious metals and inhibits agglomeration. The electronic interaction between the carrier and the precious metal can effectively improve the activity of the catalyst. In addition, the price of the carrier is generally low, which directly reduces the overall cost of the catalyst. Therefore, supported catalysts have been widely studied in the application of acidic oxygen evolution reaction. Many carrier materials have been used in oxygen evolution reaction catalysts and have achieved good results. However, there is no research on the support material of yttrium-doped titanium oxide compounds for anode catalysts for hydrogen production by water electrolysis. Summary of the invention
[0005] The purpose of the present disclosure is to provide a supported iridium-containing catalyst and a preparation method and application thereof. When the catalyst is used as an anode catalyst for proton exchange membrane water electrolysis to produce hydrogen, it has the characteristics of low overpotential, high activity and good cycle stability.
[0006] In order to achieve the above-mentioned object, the present disclosure provides a supported iridium-containing catalyst in a first aspect, wherein the supported iridium-containing catalyst comprises a carrier and an active component supported on the carrier;
[0007] The carrier includes yttrium-doped titanium oxide, and the active component includes one or more of simple Ir, IrO and IrO2.
[0008] Optionally, the content of yttrium is 0.1-1.5 wt % relative to the total weight of the yttrium-doped titanium oxide compound, wherein the weight of the yttrium is calculated as yttrium element, and the total weight of the yttrium-doped titanium oxide compound is calculated as titanium dioxide and yttrium element;
[0009] The average pore size of the carrier is 5-10nm, and the specific surface area is 10-70m 2 / g, with a total pore volume of 0.012-0.153 cm 3 / g;
[0010] m Ti3+ / (m Ti3+ +m Ti4+ ) is 0.02-0.16;
[0011] m Ti3+ represents the content of positive trivalent titanium on the surface of the yttrium-doped titanium oxide compound, m Ti4+ represents the content of tetravalent titanium on the surface of the yttrium-doped titanium oxide;
[0012] O α / (O α +O β ) is 0.31-0.40;
[0013] O α represents the content of non-lattice oxygen on the surface of the yttrium-doped titanium oxide compound, O β It represents the content of lattice oxygen on the surface of the yttrium-doped titanium oxide.
[0014] Optionally, the catalyst has an average pore size of 2.1-8.0 nm and a specific surface area of 30-92 m 2 / g, with a total pore volume of 0.017-0.063 cm 3 / g.
[0015] Optionally, relative to the total weight of the yttrium-doped titanium oxide compound and the active component, the content of the active component is 30-70% by weight, the weight of the active component is calculated as iridium element, and the weight of the yttrium-doped titanium oxide compound is calculated as yttrium element and titanium dioxide.
[0016] A second aspect of the present disclosure provides a method for preparing a supported iridium-containing catalyst, the method comprising: contacting an iridium source, a carrier, a reducing agent and a surfactant;
[0017] The reducing agent includes one or more saturated alcohols having 1 to 5 carbon atoms;
[0018] The support includes yttrium-doped titanium oxide.
[0019] Optionally, the content of yttrium is 0.1-1.5 wt % relative to the total weight of the yttrium-doped titanium oxide compound, wherein the weight of yttrium is calculated as yttrium element, and the total weight of the yttrium-doped titanium oxide compound is calculated as titanium dioxide and yttrium element;
[0020] The average pore size of the carrier is 5-10nm, and the specific surface area is 10-70m 2 / g, with a total pore volume of 0.012-0.153 cm 3 / g;
[0021] m Ti3+ / (m Ti3+ +m Ti4+ ) is 0.02-0.16;
[0022] m Ti3+ represents the content of positive trivalent titanium on the surface of the yttrium-doped titanium oxide compound, m Ti4+ represents the content of tetravalent titanium on the surface of the yttrium-doped titanium oxide;
[0023] O α / (O α +O β ) is 0.31-0.40;
[0024] O α represents the content of non-lattice oxygen on the surface of the yttrium-doped titanium oxide compound, O β It represents the content of lattice oxygen on the surface of the yttrium-doped titanium oxide.
[0025] Optionally, the iridium source includes one or more of IrCl3, chloroiridic acid and Ir(acac)3;
[0026] The surfactant includes one or more of quaternary ammonium salts having 15 to 20 carbon atoms, preferably one or more of hexadecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide and hexadecyltrimethylammonium bromide;
[0027] The reducing agent includes one or more of a saturated monohydric alcohol having 1 to 5 carbon atoms and a saturated dihydric alcohol having 2 to 5 carbon atoms, and preferably includes one or more of ethylene glycol, propylene glycol and n-butanol.
[0028] Optionally, the amount of the iridium source is 30-70% by weight relative to the total weight of the yttrium-doped titanium oxide compound and the iridium source, the weight of the iridium source is calculated as iridium element, and the weight of the yttrium-doped titanium oxide compound is calculated as yttrium element and titanium dioxide;
[0029] The weight ratio of the iridium source to the surfactant, calculated as iridium element, is 1:(1-20);
[0030] The amount of the reducing agent used is 50-2000 mL relative to 1 g of the iridium source calculated as iridium element.
[0031] Optionally, the contact reaction conditions include: time of 3-6 hours and temperature of 140-180°C.
[0032] Optionally, the method comprises the following steps:
[0033] S1, performing a first mixing of the surfactant, the carrier and the reducing agent to obtain a first mixture;
[0034] S2, performing a second mixing of the iridium source and the first mixture, and then performing the contact reaction;
[0035] Wherein, the first mixing time is 1-4h;
[0036] The second mixing time is 2-4 hours.
[0037] The third aspect of the present disclosure provides a supported iridium-containing catalyst prepared by the method described in the second aspect of the present disclosure.
[0038] The fourth aspect of the present disclosure provides the use of the supported iridium-containing catalyst described in the first aspect or the third aspect of the present disclosure as an anode catalyst in electrochemistry.
[0039] The fifth aspect of the present disclosure provides a proton exchange membrane water electrolysis device, comprising a proton exchange membrane, a cathode catalyst layer, an anode catalyst layer, a cathode diffusion layer and an anode diffusion layer, wherein the anode catalyst layer comprises the supported iridium-containing catalyst described in the first aspect or the third aspect of the present disclosure.
[0040] The sixth aspect of the present disclosure provides a method for producing hydrogen by electrolyzing water, using the supported iridium-containing catalyst described in the first aspect or the third aspect of the present disclosure, or using the proton exchange membrane water electrolysis device described in the fifth aspect of the present disclosure.
[0041] Through the above technical solution, the present application uses a carrier containing yttrium-doped titanium oxide compounds to load iridium-containing substances as active components, and the beneficial effects include:
[0042] (1) The catalyst disclosed in the present invention has good oxidation resistance and acid resistance, and will not dissolve under harsh conditions of strong acid and high potential; and has good catalytic activity. When used as an anode catalyst for proton exchange membrane water electrolysis to produce hydrogen, it has the characteristics of low overpotential, high activity and good cycle stability;
[0043] (2) The catalyst disclosed in the present invention uses yttrium-doped titanium oxide as a carrier, and the carrier transfers electrons to the active component, thereby improving the interaction between the carrier and the active component, thereby improving the catalytic activity of the catalyst;
[0044] (3) The active components in the catalyst disclosed in the present invention have high dispersion and good continuity on the carrier, which can reduce the amount of precious metals while ensuring the catalytic performance;
[0045] (4) The catalyst disclosed in the present invention is in powder form, which is convenient for preparing large-area membrane electrode materials and is suitable for PEM water electrolysis;
[0046] (4) The present invention adopts a liquid phase reduction method to prepare a supported iridium-containing catalyst, which can avoid the agglomeration of active components and has the advantages of simple operation, low cost, good repeatability, and large-scale batch production.
[0047] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0049] Figure 1 This is the isothermal adsorption-desorption curve of the yttrium-doped titanium oxide support prepared in Example 1 of the present disclosure.
[0050] Figure 2 This is a SEM image of the yttrium-doped titanium oxide support prepared in Example 1 of the present disclosure.
[0051] Figure 3 This is a TEM image of the yttrium-doped titanium oxide support prepared in Example 1 of the present disclosure.
[0052] Figure 4 This is a TEM image of the supported iridium-containing catalyst A1 prepared in Example 1 of the present disclosure.
[0053] Figure 5 This is a polarization curve diagram of the supported iridium-containing catalyst A1 prepared in Example 1 of the present disclosure in 0.5 mol / L H2SO4 solution.
[0054] Figure 6 This is the XRD pattern of the supported iridium-containing catalyst A1 prepared in Example 1 of the present disclosure.
[0055] Figure 7 This is the XPS chart of the supported iridium-containing catalyst A1 prepared in Example 1 of the present disclosure.
[0056] Figure 8 This is a polarization curve diagram of the supported iridium-containing catalyst A2 prepared in Example 2 of the present disclosure in 0.5 mol / L H2SO4 solution.
[0057] Fig. 9 This is the XRD pattern of the supported iridium-containing catalyst A2 prepared in Example 2 of the present disclosure.
[0058] Fig.10 Polarization curves of supported iridium-containing catalysts A3 and A4 prepared in Examples 3 and 4 of the present disclosure in 0.5 mol / L H2SO4 solution.
[0059] Fig.11 Polarization curves of the anode catalysts prepared in Example 1 and Comparative Examples 1 and 2 of the present disclosure in 0.5 mol / L H2SO4 solution.
[0060] Fig.12 XPS spectra of O1s energy level of yttrium-doped and undoped titanium oxide compounds.
[0061] Fig.13 XPS spectra of Ti 2p energy levels of yttrium-doped and undoped titanium oxides. DETAILED DESCRIPTION
[0062] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0063] The first aspect of the present disclosure provides a supported iridium-containing catalyst, the supported iridium-containing catalyst comprising a carrier and an active component supported on the carrier;
[0064] The carrier includes yttrium-doped titanium oxide, and the active component includes one or more of simple Ir, IrO and IrO2.
[0065] In the present disclosure, the active components are loaded on the surface of the carrier, and optionally distributed inside the pores of the carrier, preferably distributed on the surface and inside the pores of the carrier.
[0066] In the present disclosure, the active component may include any one, any two or three of elemental Ir, IrO and IrO2. When the active component includes more than two substances, there is no restriction on the ratio, that is, any ratio can achieve the technical effect of the present disclosure.
[0067] In the present disclosure, the "titanium oxide compound" in the yttrium-doped titanium oxide compound may include titanium dioxide and / or titanium trioxide. The present disclosure has no limitation on the crystal form of the titanium oxide compound. For example, it may have an anatase single-phase crystal form or a rutile crystal form. Yttrium is doped into the titanium oxide compound lattice to form oxygen vacancies and have a higher specific surface area, which is beneficial to the loading of active components and can enhance the interaction between the active components and the carrier, thereby improving the catalytic activity of the catalyst.
[0068] According to one embodiment of the present disclosure, the average particle size of the active component is 1-10 nm, preferably 1.5-5.5 nm; the active component with the above size has a strong loading capacity and is not easy to fall off.
[0069] According to one embodiment of the present disclosure, the yttrium content is 0.1-1.5% by weight, preferably 0.5-1% by weight, relative to the total weight of the yttrium-doped titanium oxide compound, wherein the weight of yttrium is calculated as yttrium element, and the total weight of the yttrium-doped titanium oxide compound is calculated as titanium dioxide and yttrium element; the yttrium-doped titanium oxide compound carrier having the above content has a suitable specific surface area, which is beneficial to the loading of active components, thereby improving the catalytic activity of the catalyst.
[0070] According to one embodiment of the present disclosure, the average pore size of the carrier is 5-10 nm, and the specific surface area is 10-70 m 2 / g, with a total pore volume of 0.012-0.153 cm 3 / g; The carrier having the above characteristics is conducive to the diffusion of reactant molecules into the pores of the catalyst for reaction, and is conducive to the active components being loaded on the carrier to form a continuous conductive path, thereby improving the catalytic activity of the catalyst.
[0071] According to one embodiment of the present disclosure, the average pore size of the catalyst is 2.1-8.0 nm, and the specific surface area is 30-92 m 2 / g, with a total pore volume of 0.017-0.063 cm 3 / g; The catalyst having the above characteristics is conducive to the diffusion of reactants, and the active components are evenly dispersed on the carrier. When used as an anode catalyst for water electrolysis, it has the characteristics of low overpotential, high activity and good cycle stability.
[0072] According to one embodiment of the present disclosure, m Ti3+ / (m Ti3+ +m Ti4+ ) is 0.02-0.16; m Ti3+ represents the content of positive trivalent titanium on the surface of the yttrium-doped titanium oxide compound, m Ti4+ represents the content of positive tetravalent titanium on the surface of the yttrium-doped titanium oxide; α / (O α +O β ) is 0.31-0.40; α represents the content of non-lattice oxygen on the surface of the yttrium-doped titanium oxide compound, O βRepresents the content of lattice oxygen on the surface of the yttrium-doped titanium oxide compound; wherein, "the content of positive trivalent titanium on the surface of the yttrium-doped titanium oxide compound" refers to the content ratio of trivalent titanium ions on the surface relative to the total amount of the titanium oxide compound; "the content of positive tetravalent titanium on the surface of the yttrium-doped titanium oxide compound" refers to the content ratio of tetravalent titanium ions on the surface relative to the total amount of the titanium oxide compound; "the content of non-lattice oxygen on the surface of the yttrium-doped titanium oxide compound" refers to the content ratio of non-lattice oxygen on the surface relative to the total amount of non-lattice oxygen and lattice oxygen; "the content of lattice oxygen on the surface of the yttrium-doped titanium oxide compound" refers to the content ratio of lattice oxygen on the surface relative to the total amount of non-lattice oxygen and lattice oxygen; O α , O β 、m Ti3+ and m Ti4+ All were tested by XPS, content and total amount refer to weight, and “surface” refers to the outer surface of the sample.
[0073] According to one embodiment of the present disclosure, relative to the total weight of the yttrium-doped titanium oxide compound and the active component, the content of the active component is 30-70% by weight, preferably 40-60% by weight, and further preferably 45-55% by weight, wherein the weight of the active component is calculated as iridium element, and the weight of the yttrium-doped titanium oxide compound is calculated as yttrium element and titanium dioxide; the catalyst having the above composition can reduce the loading amount of the active component while improving the mass specific activity, has a high utilization rate of precious metals, can form a continuous conductive path, and has high catalytic activity.
[0074] A second aspect of the present disclosure provides a method for preparing a supported iridium-containing catalyst, the method comprising: contacting an iridium source, a carrier, a reducing agent and a surfactant;
[0075] The reducing agent includes one or more saturated alcohols having 1 to 5 carbon atoms;
[0076] The support includes yttrium-doped titanium oxide.
[0077] According to one embodiment of the present disclosure, the yttrium content is 0.1-1.5 wt.%, preferably 0.5-1 wt.%, relative to the total weight of the yttrium-doped titanium oxide compound, wherein the weight of yttrium is calculated as yttrium element, and the total weight of the yttrium-doped titanium oxide compound is calculated as titanium dioxide and yttrium element.
[0078] According to one embodiment of the present disclosure, the average pore size of the carrier is 5-10 nm, and the specific surface area is 10-70 m 2 / g, with a total pore volume of 0.012-0.153 cm 3 / g.
[0079] According to one embodiment of the present disclosure, the iridium source includes one or more of IrCl3, chloroiridic acid and Ir(acac)3.
[0080] According to one embodiment of the present disclosure, the surfactant includes one or more quaternary ammonium salts with a carbon number of 15-20, preferably including one or more of cetyltrimethylammonium chloride (CTAC), tetradecyltrimethylammonium bromide (TTAB) and cetyltrimethylammonium bromide (CTAB), specifically cetyltrimethylammonium bromide (CTAB); the addition of the surfactant can disperse the carrier in the reducing agent.
[0081] According to one embodiment of the present disclosure, the reducing agent includes one or more of a saturated monohydric alcohol having 1 to 5 carbon atoms and a saturated dihydric alcohol having 2 to 5 carbon atoms, preferably one or more of ethylene glycol, propylene glycol and n-butanol.
[0082] According to one embodiment of the present disclosure, relative to the total weight of the yttrium-doped titanium oxide compound and the iridium source, the amount of the iridium source is 30-70% by weight, preferably 40-60% by weight, and further preferably 45-55% by weight. The weight of the iridium source is calculated as iridium element, and the weight of the yttrium-doped titanium oxide compound is calculated as yttrium element and titanium dioxide.
[0083] According to one embodiment of the present disclosure, the weight ratio of the iridium source calculated as iridium element to the surfactant is 1:(1-20); preferably 1:(5-15).
[0084] According to one embodiment of the present disclosure, the amount of the reducing agent used is 50-2000 mL, preferably 150-1500 mL, relative to 1 g of the iridium source calculated as the iridium element.
[0085] According to one embodiment of the present disclosure, the conditions for the contact reaction include: a time of 3-6 hours and a temperature of 140-180° C.; the contact reaction method can be, for example, heating, condensing and reflux; carrying out the contact reaction under the above conditions can avoid the agglomeration of active components and improve the catalytic activity.
[0086] According to one embodiment of the present disclosure, the method comprises the following steps:
[0087] S1, mixing the surfactant, the carrier and the reducing agent for the first time to obtain a first mixture;
[0088] S2, mixing the iridium source with the first mixture for a second time, and then performing a contact reaction;
[0089] The first mixing time is 1-4h, and the second mixing time is 2-4h; the mixing method can be, for example, stirring, and the temperature can be, for example, room temperature (25°C); the contact reaction using the above method can make the active components more evenly loaded on the carrier, thereby improving the activity of the catalyst.
[0090] According to one embodiment of the present disclosure, the method further includes: cooling the mixed material obtained by the contact reaction to room temperature, and then washing, solid-liquid separation and drying; wherein the washing method may, for example, be: washing under ultrasonic conditions using ultrapure water at room temperature (25°C) until there are no chloride ions in the washing liquid when silver nitrate is used to detect or the pH value of the washing liquid at room temperature (25°C) is neutral; the solid-liquid separation method is conventional in the art, for example, it may be centrifugal separation, and the conditions for centrifugal separation are conventional and will not be elaborated herein; the drying method is conventional in the art, for example, it may be dried overnight in a freeze dryer, and the drying temperature may be -40 to -20°C.
[0091] According to one embodiment of the present disclosure, the preparation method of the yttrium-doped titanium oxide compound is conventional in the art, for example, it can be prepared by a sol-gel method. The titanium oxide compound prepared by the above method has an anatase single-phase crystal form. The method may specifically include the following steps:
[0092] a. Mixing the titanium source and the first alcohol raw material, adjusting the pH value of the mixture to 1-3 (at room temperature) to obtain a first material;
[0093] b. mixing the yttrium source, water and the second alcohol raw material to obtain a second material;
[0094] c. mixing the first material and the second material to obtain a gel;
[0095] d. drying the gel to obtain a solid mixture;
[0096] e. calcining, washing, solid-liquid separation and drying the solid mixture to obtain a yttrium-doped titanium oxide carrier;
[0097] Wherein, relative to the total weight of the yttrium source and the titanium source, the amount of the yttrium source is 0.1-1.5% by weight, preferably 0.5-1% by weight, wherein the weight of the yttrium source is calculated as yttrium element, and the weight of the titanium source is calculated as titanium dioxide;
[0098] The first alcohol raw material and the second alcohol raw material are the same or different, and respectively include one or more of anhydrous ethanol, isopropanol and n-butanol;
[0099] The titanium source includes one or more of tetrabutyl titanate, tetraisopropyl titanate and titanium tetrachloride;
[0100] The yttrium source includes one or more of yttrium nitrate hexahydrate, yttrium chloride and yttrium oxide;
[0101] The method for adjusting the pH value is conventional in the art, such as adding hydrochloric acid, and there is no specific limitation on the concentration of hydrochloric acid;
[0102] Step c comprises: adding the second material dropwise to the first material within 5-15 minutes, stirring and mixing at room temperature (25° C.) for 1-4 hours, and then standing for 20-30 hours to obtain a gel;
[0103] In step d, the drying method is conventional in the art, for example, it can be dried in a drying oven, and the drying conditions include: time of 2-5h, temperature of 80-120°C;
[0104] In step e, the calcination conditions include: a heating rate of 2-4°C / min, a time of 2-5h, and a temperature of 450-600°C;
[0105] In step f, the washing method may be, for example, washing with ultrapure water under ultrasonic conditions at room temperature (25° C.) until the pH value of the washing solution at room temperature (25° C.) is 7; the solid-liquid separation method is conventional in the art, for example, it may be centrifugal separation, and the conditions for centrifugal separation are conventional and will not be described in detail here; the drying method is conventional in the art, for example, it may be dried in a drying oven overnight, and the drying temperature is 50-70° C.;
[0106] The method further comprises: grinding the solid mixture before calcining.
[0107] The third aspect of the present disclosure provides a supported iridium-containing catalyst prepared by the method described in the second aspect of the present disclosure. The catalyst has the same characteristics as the catalyst described in the first aspect of the present disclosure, which will not be described in detail here.
[0108] The fourth aspect of the present disclosure provides the use of the supported iridium-containing catalyst described in the first aspect or the third aspect of the present disclosure as an anode catalyst in electrochemistry.
[0109] The fifth aspect of the present disclosure provides a proton exchange membrane water electrolysis device, comprising a proton exchange membrane, a cathode catalyst layer, an anode catalyst layer, a cathode diffusion layer and an anode diffusion layer, wherein the anode catalyst layer comprises the supported iridium-containing catalyst described in the first aspect or the third aspect of the present disclosure.
[0110] The sixth aspect of the present disclosure provides a method for producing hydrogen by electrolyzing water, using the supported iridium-containing catalyst described in the first aspect or the third aspect of the present disclosure, or using the proton exchange membrane water electrolysis device described in the fifth aspect of the present disclosure.
[0111] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form.
[0112] Reagents, Instruments and Tests
[0113] The raw materials used in the examples and comparative examples were all purchased from commercial sources and were of analytical grade unless otherwise specified.
[0114] In the examples and comparative examples, the chloroiridic acid raw material is in liquid form, and the mass fraction of iridium is 35%; yttrium nitrate hexahydrate is purchased from Aladdin Reagent Co., Ltd. (Aladdin).
[0115] O α , O β 、m Ti3+ and m Ti4+ All tested by XPS.
[0116] Instruments, methods and conditions for TEM analysis: The model of the high-resolution transmission electron microscope (HRTEM) used in the present disclosure is JEM-2100 (HRTEM) (JEOL Ltd.), and the test conditions of the high-resolution transmission electron microscope are: the acceleration voltage is 200 kV.
[0117] Instruments, methods and conditions for XPS analysis: The present invention uses an X-ray photoelectron spectroscopy (XPS) to detect the elements on the surface of the material. The X-ray photoelectron spectroscopy used is an ESCALab220i-XL type X-ray electron spectrometer equipped with Avantage V5.926 software produced by VG Scientific. The X-ray photoelectron spectroscopy analysis test conditions are as follows: the excitation source is monochromatic A1Kα X-ray, the power is 330W, and the basic vacuum during the analysis test is 3×10 -9 In addition, the electron binding energy was calibrated using the C1s peak (284.8 eV) of elemental carbon.
[0118] Instruments, methods and conditions for XRD analysis: X-ray diffraction analysis (XRD) was performed on a Shimadzu XRD-6000 X-ray diffractometer, Japan. The test conditions included: tube voltage 40 kV, tube current 40 mA, Cu target Kα radiation, 2θ scanning range 5° to 80°. The characteristic peak area was calculated using MDI Jade 6 software, and the peak area was calculated by deducting the background, locating the peak position, and fitting the peaks to minimize the residual.
[0119] BET test method: In the present disclosure, the pore structure properties are measured by a Quantachrome AS-6B analyzer, the specific surface area and pore volume are obtained by the Brunauer-Emmett-Taller (BET) method, and the pore distribution curve is calculated by the desorption curve according to the Barrett-Joyner-Halenda (BJH) method.
[0120] Conductivity test method: The conductivity test was conducted on the FT-301B automatic conductor powder resistivity tester. The test conditions included pressure requirement of 3.9MPa±0.03MPa, inner diameter of powder mold of 16mm-16.3mm; height measurement range: 15-17mm, test current of 500mA. Conductivity 5×10 -7 -10 7 s / cm.
[0121] Electrochemical activity test: A three-electrode system was used, with a glassy carbon electrode as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum sheet as the counter electrode. The electrolyte used under acidic conditions was a 0.5 mol / L H2SO4 solution, and the temperature was controlled by a constant temperature water bath at 25°C. 5 mg of the catalyst to be tested was ultrasonically uniformly dispersed in a mixed solution of 0.3 mL isopropanol, 0.6 mL water, and 0.1 mL (5% Nafion) solution (perfluorosulfonic acid polymer solution) (the mass ratio of the catalyst to Nafion was 1:1), and then dropped onto the surface of the glassy carbon electrode. After natural drying, the working electrode was obtained. Before the test, oxygen was passed through the electrolyte for 30 minutes to saturate the solution with oxygen. The scanning interval of the cyclic voltammetry curve (CV) was 0-1.2 V (vs. SCE), the scanning rate was 50 mV / s, and the scanning interval of the linear polarization curve (LSV) was 1.2-1.5 V (vs. RHE), and the scanning rate was 5 mV / s. The electrode rotation speed was 2500 rpm.
[0122] Preparation of membrane electrode assembly: The prepared catalyst is made into a membrane electrode assembly using catalyst coating membrane technology (the anode catalyst uses the catalyst prepared in the embodiment and the comparative example, and the cathode catalyst uses 40wt% Pt / C (commercial product of JM Company)). The specific steps are as follows:
[0123] (1) Membrane pretreatment:
[0124] A square Nafion 117 membrane (thickness 183 μm) with a side length of 50 mm was immersed in ultrapure water and rinsed several times;
[0125] (2) Preparation of catalyst dispersion:
[0126] The cathode catalyst uses a commercial platinum carbon catalyst (40wt% Pt / C), and the anode uses the catalysts of the examples and comparative examples. Isopropanol and ultrapure water are mixed in a volume ratio of 7:3 as a catalyst dispersion medium, and then catalyst powder and Nafion membrane solution are added. After the mixture is prepared, ultrasonic vibration is performed for 1 hour to obtain a uniformly dispersed catalyst slurry;
[0127] (3) Spraying catalyst:
[0128] Place the PEM membrane washed with ultrapure water on the heating plate of the sprayer and press it flat to dry. Use a sprayer with an ultrasonic dispersion nozzle to spray the cathode and cathode catalyst dispersions evenly onto both sides of the dried Nafion 117 membrane. Control the heating temperature to 40-50°C and the spraying amount to 1 mg (Pt) cm for the cathode Pt content. -2 , the Ir element content of the anode is 2mg(Ir)·cm -2 .
[0129] Membrane electrode (MEA) test: The components were fixed into a single electrolysis cell, and preheated deionized water was pumped through a horizontal flow pump at a rate of 200 ml / min. -1 The flow rate is passed into the anode, and the water inlet temperature is 80℃. The input current is adjusted by the constant current mode of the voltage-stabilized DC power supply, and the slot voltage between the two-electrode titanium flow field plates is read. The test range is 0.01-1A·cm -2 .
[0130] Example 1
[0131] The supported iridium-containing catalyst A1 was prepared by the following steps:
[0132] (1) 30 mL of anhydrous ethanol was placed in a beaker and stirred at room temperature, and 10 mL of tetrabutyl titanate was slowly added dropwise to the beaker. After mixing, 1 mL of hydrochloric acid was added to control the pH value to 3 to obtain a first material;
[0133] (2) dissolving 0.08 g of yttrium nitrate hexahydrate in a mixture of 2 mL of ultrapure water and 4 mL of anhydrous ethanol to obtain a second material;
[0134] (3) slowly adding the second material dropwise into the first material within 10 min, stirring and mixing in a beaker at room temperature (25° C.) for 3 h, and then standing for 24 h to obtain a gel;
[0135] (4) drying the gel in step (3) in an oven at 100° C. for 4 h to obtain a solid mixture;
[0136] (5) Grinding the solid mixture of step (4), spreading it flat into a calcining dish, placing it in a muffle furnace, heating it to 550° C. at a heating rate of 3° C. / min, and calcining it for 3 h;
[0137] (6) After cooling to room temperature, a certain amount of ultrapure water was added for ultrasonic washing and centrifugation (10000 rpm, 10 min) 3 times until the pH value of the solution at room temperature (25° C.) was 7, and the solution was placed in a 60° C. oven for drying overnight, and after grinding, a yttrium-doped titanium oxide support was obtained;
[0138] Relative to the total weight of the yttrium source and the titanium source, the amount of the yttrium source is 1 wt %, the weight of the yttrium source is calculated as yttrium element, and the weight of the titanium source is calculated as titanium dioxide;
[0139] (7) dissolving 1.124 g of hexadecyltrimethylammonium bromide (CTAB) in 80 mL of ethylene glycol, adding 40 mg of the yttrium-doped titanium oxide support prepared in step (6) in terms of yttrium element and titanium dioxide, stirring and mixing for 1 h to obtain a first mixture; then adding 0.172 g of H2IrCl6·xH2O (chloroiridic acid, iridium content of 35 wt%) to the first mixture, stirring and mixing for 2 h, and then condensing and refluxing at 160° C. for 3 h to obtain a mixed material;
[0140] The amount of the iridium source is 60% by weight relative to the total weight of the yttrium-doped titanium oxide carrier and the iridium source, the weight of the iridium source is calculated as iridium element, and the weight of the yttrium-doped titanium oxide is calculated as yttrium element and titanium dioxide;
[0141] The weight ratio of the iridium source to the surfactant, calculated as iridium element, is 1:20;
[0142] The amount of reducing agent used is 1330 mL relative to 1 g of iridium source calculated as iridium element;
[0143] (8) After the mixture is cooled to room temperature, a certain amount of ultrapure water is added for ultrasonic washing and centrifugation (10000 rpm, 10 min) for 4 times until no chloride ions are found in the washing solution using silver nitrate detection; the mixture is then placed in a freeze dryer and dried overnight at a temperature of -20°C; after grinding, a supported iridium-containing catalyst A1 is obtained, and its parameters are listed in Table 1.
[0144] Example 2
[0145] The supported iridium-containing catalyst A2 was prepared by the method of Example 1, except that in step (7), the amount of iridium source used was 50% by weight relative to the total weight of the yttrium-doped titanium oxide carrier and the iridium source. The parameters of catalyst A2 are listed in Table 1.
[0146] Example 3
[0147] The supported iridium-containing catalyst A3 was prepared by the method of Example 1, except that in step (7), the amount of iridium source used was 40% by weight relative to the total weight of the yttrium-doped titanium oxide carrier and the iridium source. The parameters of catalyst A3 are listed in Table 1.
[0148] Example 4
[0149] The supported iridium-containing catalyst A4 was prepared by the method of Example 1, except that in step (1), 2.5 mL of hydrochloric acid was added after mixing to control the pH value to 2. The parameters of catalyst A4 are listed in Table 1.
[0150] Example 5
[0151] The supported iridium-containing catalyst A5 was prepared by the method of Example 1, except that in step (6), the amount of yttrium source used was 1.5 wt % relative to the total weight of the yttrium source and the titanium source. The parameters of catalyst A5 are listed in Table 1.
[0152] XRD tests were performed on the supports prepared in Examples 1-5 above, and the titanium oxide compounds therein were all in anatase configuration.
[0153] Comparative Example 1
[0154] The supported iridium-containing catalyst D1 was prepared by the method of Example 1, except that in step (7), commercial anatase titanium dioxide was used as a carrier. The parameters of the catalyst D1 are listed in Table 1.
[0155] Comparative Example 2
[0156] The supported iridium-containing catalyst D2 was prepared by the method of Example 1, except that yttrium nitrate hexahydrate was not added in step (2). The parameters of catalyst D2 are listed in Table 1.
[0157] Comparative Example 3
[0158] Commercial IrO2 (Chunhua) catalyst D3.
[0159] Comparative Example 4
[0160] Commercial iridium black (Heraeus) catalyst D4.
[0161] Table 1
[0162]
[0163] According to the data in Table 1, the supported iridium-containing catalyst prepared by the method disclosed in the present invention has the advantages of high catalytic activity and good stability. When used as an anode catalyst for hydrogen production by proton exchange membrane electrolysis of water, it has the characteristics of low overpotential, high activity and good cycle stability. Furthermore, compared with Comparative Examples 1 and 2 in which undoped yttrium-doped titanium oxide compounds are used as carriers, the proportion of non-lattice oxygen on the surface of the yttrium-doped titanium oxide carrier increases, and the Ti 3+ The content proportion also becomes larger, indicating that after yttrium doping, the oxygen vacancies in the titanium oxide compound increase, the electron transfer ability is enhanced, and the catalytic activity of the prepared catalyst is higher; specifically, relative to the undoped yttrium catalyst, the overpotential of the yttrium-doped catalyst is increased by at most about 45 mV; according to the data comparison of Examples 1-3, it can be seen that when the content of the active component is in the range of 45-55 weight %, the activity of the catalyst is better.
[0164] XPS binding energy test was performed on the catalysts of the examples and comparative examples, and the results are shown in Table 2. According to the data in Table 2, it can be seen that the active component in catalysts A1-A5 is single substance Ir.
[0165] Table 2
[0166] Example / Comparative Example No. Catalyst No. <![CDATA[Binding energy (Ir 4f 7 / 2 / eV)]]> Example 1 A1 61.14 Example 2 A2 61.01 Example 3 A3 61.11 Example 4 A4 61.08 Example 5 A5 61.05 Comparative Example 1 D1 61.05 Comparative Example 2 D2 61.13 Comparative Example 3 D3 61.81 Comparative Example 4 D4 61.20
[0167] The stability test of the catalyst A1 prepared in Example 1 was carried out. The specific method was as follows: the components were fixed into a single electrolysis cell, and preheated deionized water was pumped through a horizontal flow pump at a rate of 200 mL min -1 The flow rate is passed into the anode, and the water inlet temperature is 80℃. The input current is adjusted by the constant current mode of the voltage-stabilized DC power supply, and the slot voltage between the two-electrode titanium flow field plates is read. The test range is 0.01-1A·cm -2 After multiple cycles of current flow, a stable value is reached (the voltage does not change compared to the previous cycle).
[0168] The results are shown in Table 3. According to the data in Table 3, the catalyst prepared in the present disclosure has good stability and is less soluble or even insoluble under strong acid and high potential.
[0169] Table 3
[0170] <![CDATA[Current density / A / cm 2 > Voltage / V 0.4 1.36 0.6 1.45 0.8 1.51 1 1.60
[0171] The carrier prepared in Example 1 was subjected to isothermal adsorption-desorption test, SEM test and TEM test, and the results were as follows: Figure 1 , 2 and 3.
[0172] The catalyst A1 prepared in Example 1 was subjected to TEM test, and the results were as follows: Figure 4 shown.
[0173] The catalyst A1 prepared in Example 1 was subjected to polarization curve test in 0.5 mol / L H2SO4 solution. The results are as follows: Figure 5 shown.
[0174] The catalyst A1 prepared in Example 1 was subjected to XRD and XPS tests, and the results were as follows: Figure 6 and 7 As shown; Figure 6 There is a sharp characteristic peak at 25.6°, indicating that it has an anatase crystal form.
[0175] The catalyst A2 prepared in Example 2 was subjected to polarization curve test in 0.5 mol / L H2SO4 solution. The results are as follows: Figure 8 shown.
[0176] The catalyst A2 prepared in Example 2 was subjected to XRD testing, and the results were as follows: Fig. 9 shown.
[0177] The catalysts A3 and A4 prepared in Examples 3 and 4 were subjected to polarization curve tests in 0.5 mol / L H2SO4 solution. The results are as follows: Fig.10 As shown;
[0178] Among them, the curve of catalyst A3 is a, and the curve of catalyst A4 is b.
[0179] Polarization curves of catalysts A1, D1 and D2 prepared in Example 1, Comparative Example 1 and Comparative Example 2 were tested in 0.5 mol / L H2SO4 solution. Fig.11 As shown;
[0180] Among them, the curve of catalyst A1 is c, the curve of catalyst D1 is d, and the curve of catalyst D2 is e.
[0181] Fig.12 XPS spectra of O1s energy level of yttrium-doped and undoped titanium oxide compounds; f corresponds to yttrium doping amount of 0, and h corresponds to yttrium doping amount of 1 weight %.
[0182] Fig.13 XPS spectra of Ti 2p energy levels of yttrium-doped and undoped titanium oxide compounds; m corresponds to a yttrium doping amount of 0, and k corresponds to a yttrium doping amount of 1 weight %.
[0183] according to Figure 4 The results show that the precious metals are highly dispersed and continuous on the carrier, and the catalyst particles are uniform.
[0184] according to Figure 5 , 8 As can be seen from the results of , 10 and 11, the catalyst prepared in the examples of the present disclosure has a higher catalytic activity.
[0185] Figure 6 and 9 The results show that when the content of the active component decreases from 60 wt % to 50 wt %, the particle size of the active component is smaller and the utilization rate is higher.
[0186] according to Figure 7 The results show that the active component of the catalyst is single substance Ir.
[0187] according to Fig.12 From the results, it can be seen that there are three peaks in the XPS spectrum of the O1s energy level of undoped yttrium titanium oxide compounds, and the peaks at binding energies of 529.87eV, 531.87eV and 533.33eV are attributed to lattice oxygen, non-lattice oxygen and surface hydroxyl groups, respectively; after yttrium doping, the binding energy of lattice oxygen changes from 529.87eV to 529.69eV, and the peak areas corresponding to lattice oxygen and surface hydroxyl groups are greatly increased, indicating that yttrium is doped into the lattice of titanium oxide compounds and oxygen vacancies are formed.
[0188] according to Fig.13 The results show that the binding energies of the double peaks Ti 2p3 / 2 and Ti 2p1 / 2 are 458.47 eV and 464.17 eV, respectively, indicating the presence of the +IV oxidation state of Ti in the lattice of the titanium oxide compound; the peak of Ti 2p1 / 2 at a binding energy of 460.31 eV corresponds to the +III oxidation state of Ti; after yttrium doping, Ti 3+ The corresponding peak area increases, Ti 4+ The corresponding peak area decreases; the above shows that yttrium doping will form oxygen vacancies in titanium oxide compounds, and the cations near the oxygen vacancies will be reduced, thereby triggering the electronic interaction between the reduced cations and the precious metal atoms, thereby generating yttrium-titanium oxide interaction, thereby promoting the improvement of electrical conductivity.
[0189] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0190] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0191] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A supported iridium-containing catalyst, characterized in that The supported iridium-containing catalyst comprises a carrier and an active component supported on the carrier; The carrier includes yttrium-doped titanium oxide, and the active component includes one or more of simple Ir, IrO and IrO2.
2. The supported iridium-containing catalyst according to claim 1, wherein The content of yttrium is 0.1-1.5% by weight relative to the total weight of the yttrium-doped titanium oxide compound, wherein the weight of the yttrium is calculated as yttrium element, and the total weight of the yttrium-doped titanium oxide compound is calculated as titanium dioxide and yttrium element; The average pore size of the carrier is 5-10nm, and the specific surface area is 10-70m 2 / g, with a total pore volume of 0.012-0.153 cm 3 / g; m Ti3+ / (m Ti3+ +m Ti4+ ) is 0.02-0.16; m Ti3+ represents the content of positive trivalent titanium on the surface of the yttrium-doped titanium oxide compound, m Ti4+ represents the content of tetravalent titanium on the surface of the yttrium-doped titanium oxide; O α / (O α +O β ) is 0.31-0.40; O α represents the content of non-lattice oxygen on the surface of the yttrium-doped titanium oxide compound, O β It represents the content of lattice oxygen on the surface of the yttrium-doped titanium oxide.
3. The supported iridium-containing catalyst according to claim 1, wherein The average pore size of the catalyst is 2.1-8.0 nm, and the specific surface area is 30-92 m 2 / g, with a total pore volume of 0.017-0.063 cm 3 / g.
4. The supported iridium-containing catalyst according to claim 1, wherein Relative to the total weight of the yttrium-doped titanium oxide compound and the active component, the content of the active component is 30-70% by weight, the weight of the active component is calculated as iridium element, and the weight of the yttrium-doped titanium oxide compound is calculated as yttrium element and titanium dioxide.
5. A method for preparing a supported iridium-containing catalyst, characterized in that: The method comprises: subjecting an iridium source, a carrier, a reducing agent and a surfactant to contact reaction; The reducing agent includes one or more saturated alcohols having 1 to 5 carbon atoms; The support includes yttrium-doped titanium oxide.
6. The method according to claim 5, wherein: The content of yttrium is 0.1-1.5 wt % relative to the total weight of the yttrium-doped titanium oxide compound, wherein the weight of yttrium is calculated as yttrium element, and the total weight of the yttrium-doped titanium oxide compound is calculated as titanium dioxide and yttrium element; The average pore size of the carrier is 5-10nm, and the specific surface area is 10-70m 2 / g, with a total pore volume of 0.012-0.153 cm 3 / g; m Ti3+ / (m Ti3+ +m Ti4+ ) is 0.02-0.16; m Ti3+ represents the content of positive trivalent titanium on the surface of the yttrium-doped titanium oxide compound, m Ti4+ represents the content of tetravalent titanium on the surface of the yttrium-doped titanium oxide; O α / (O α +O β ) is 0.31-0.40; O α represents the content of non-lattice oxygen on the surface of the yttrium-doped titanium oxide compound, O β It represents the content of lattice oxygen on the surface of the yttrium-doped titanium oxide.
7. The method according to claim 5, wherein: The iridium source includes one or more of IrCl3, chloroiridic acid and Ir(acac)3; The surfactant includes one or more of quaternary ammonium salts having 15 to 20 carbon atoms, preferably one or more of hexadecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide and hexadecyltrimethylammonium bromide; The reducing agent includes one or more of a saturated monohydric alcohol having 1 to 5 carbon atoms and a saturated dihydric alcohol having 2 to 5 carbon atoms, and preferably includes one or more of ethylene glycol, propylene glycol and n-butanol.
8. The method according to claim 5, wherein: The amount of the iridium source is 30-70% by weight relative to the total weight of the yttrium-doped titanium oxide compound and the iridium source, the weight of the iridium source is calculated as iridium element, and the weight of the yttrium-doped titanium oxide compound is calculated as yttrium element and titanium dioxide; The weight ratio of the iridium source to the surfactant, calculated as iridium element, is 1:(1-20); The amount of the reducing agent used is 50-2000 mL relative to 1 g of the iridium source calculated as iridium element.
9. The method according to claim 5, wherein: The contact reaction conditions include: time of 3-6 hours and temperature of 140-180°C.
10. The method according to claim 5, wherein: The method comprises the following steps: S1, performing a first mixing of the surfactant, the carrier and the reducing agent to obtain a first mixture; S2, performing a second mixing of the iridium source and the first mixture, and then performing the contact reaction; Wherein, the first mixing time is 1-4h; The second mixing time is 2-4 hours.
11. A supported iridium-containing catalyst prepared by the method described in any one of claims 5 to 10.
12. Use of the supported iridium-containing catalyst according to any one of claims 1 to 4 and 11 as an anode catalyst in electrochemistry.
13. A proton exchange membrane water electrolysis device, comprising a proton exchange membrane, a cathode catalyst layer, an anode catalyst layer, a cathode diffusion layer and an anode diffusion layer, characterized in that: The anode catalyst layer comprises the supported iridium-containing catalyst according to any one of claims 1 to 4 and 11.
14. A method for producing hydrogen by electrolyzing water, characterized in that: Use the supported iridium-containing catalyst described in any one of claims 1-4 and 11, or use the proton exchange membrane water electrolysis device described in claim 13.